PECULIARITIES OF IDENTIFICATION OF CORPSES OF DECEASED PERSONS AND SERVICEMEN UNDER MARTIAL LAW - Zarosylo, Volodymyr; Bondarenko, Olena; Shlapak, Anna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the article is to make a comprehensive study of the peculiarities of the process of identification of the bodies of deceased persons and servicemen under martial law, to identify the main problems arising during these procedures, and also to formulate practical recommendations for improving identification methods, interagency cooperation and regulatory and legal support, taking into account current challenges and international experience. Research methods: various research methods were used in the course of the work, both general scientific and special. Particular attention is paid to special methods, namely forensic and criminalistic methods. Statistical methods were also used to analyze the effectiveness of identification. The analysis of the legal framework of Ukraine and international humanitarian law was mandatory. Results: this article establishes that the most effective methods of identification of the wartime dead are DNA analysis, forensic examination, and analysis of personal belongings. It is found that the complexity of identification increases with significant damage to the bodies. The complex interaction between military structures, forensic institutions and humanitarian organizations plays an important role. The author identifies the need to improve the legal and regulatory framework for identification processes under martial law. Discussion: the author analyzes that identification of the bodies of the deceased in wartime requires a systematic approach with the use of modern technologies, in particular DNA examination. The importance of operational coordination between the Armed Forces of Ukraine, forensic experts and authorities is also emphasized. The problems of access to appropriate equipment and the lack of specialists in the combat zone were emphasized. The need to improve the legislative support for identification procedures in wartime was discussed.